The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/00220485.2011.606089
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Sustainable Development Through Role-Playing

Abstract: International audienceThe concept of sustainable development is used in everyday life by the general public, alongside researchers, institutions, and private companies. Nevertheless, its definition is far from being unequivocal. Clarifying the outline of the concept seems necessary. We have created a role-play for this purpose. Our article aims at depicting its main features and sequencing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Earlier evaluations [50] have shown that roleplay in which the participants defend a particular view of sustainable development, challenged by other views, helps students to grasp the complexity of the topic. Similarly, van der Meij et al [51], argue that collaborative play alone does not increase the learning outcomes, and indicate the potential of scripted dialogues to increase the 'level of dialogic acts', and in turn learning outcomes.…”
Section: The Climate Adaptation Gamementioning
confidence: 99%
“…Earlier evaluations [50] have shown that roleplay in which the participants defend a particular view of sustainable development, challenged by other views, helps students to grasp the complexity of the topic. Similarly, van der Meij et al [51], argue that collaborative play alone does not increase the learning outcomes, and indicate the potential of scripted dialogues to increase the 'level of dialogic acts', and in turn learning outcomes.…”
Section: The Climate Adaptation Gamementioning
confidence: 99%
“…The scripted role-play may be seen as an instrument for teaching a given content. Buchs and Blanchard (2011) explicitly avoided scripted role-plays as their aim was the “co-construction of knowledge” (p. 389).…”
Section: Drama and Role-play In Esdmentioning
confidence: 99%
“…This is why we believe that the first step toward designing Education for Sustainable Development should entail understanding its polysemy. The game that we have created is meant to reach this goal (Buchs & Blanchard, 2011).…”
Section: Sustainable Development: a Multifaceted Conceptmentioning
confidence: 99%